Analysis of the Role of Vocational Education for the Halal Tourism Development in Indonesia - Fahmi Achta Pratama; M. Wahyudi; Doni Eka Putra; Mulyadi Muslim; Hansi Effendi (Universitas Muhammadiyah Enrekang, 2023)
Halal tourism, a concept rooted in Islamic economics, holds significant potential within the global economic cycle. In Indonesia, the largest Islamic country, the prospects for the development of halal tourism are particularly promising. Vocational education is identified as a pivotal element in the efforts to cultivate the halal industry in Indonesia, playing a crucial role in this development. The research methodology employed for this study was based on library research. The stages encompassed selecting research topics, determining focal points, collecting literature reviews, preparing data presentations, and compiling the final report. A total of 12 articles published between 2010 and 2022 were analyzed, sourced from Google Scholar and Harzing via Publish or Perish, using keywords such as